(untitled) (Research, Society and Development, 2021)
This study aims to present the applicability of Assistive Technology for the performance of daily activities and promotion of functional autonomy in people with spinal cord injury. This is an integrative review carried out in the following databases: Lilacs, SCiELO, Ibecs, Bdenf, and PubMed from 2015 to 2020, using the descriptors: Assistive Technology; Spinal Cord Injuries; International Classification of Functioning, Disability and Health; Daily Activities and Physical Rehabilitation. Publications available in Portuguese, Spanish and English, published in the aforementioned databases, from 2015 to 2020 were adopted as inclusion criteria. In total, 15 international publications were included in which the following categories emerged: Assistive technology in the performance of activities and Assistive Technology in the promotion of functional autonomy. From the analysis of the articles, it was possible to observe that Assistive Technology played a fundamental role in the performance of daily activities in people with spinal cord injury, as it allowed both the performance of tasks previously limited by their condition and favored the promotion of functional autonomy.